Transport parameters of selected neonicotinoids in different aquifer materials using batch sorption tests - Pietrzak, Damian; Kania, Jarosław; Kmiecik, Ewa (Geology, Geophysics and Environment, 2022)
Contamination of surface and groundwater by neonicotinoids is a global problem and requires comprehensive action by individual countries in order to identify in detail the processes affecting the transport of these pesticides, their properties, and their harmfulness to the environment. The aim of this study was to assess the transport (expressed by sorption parameters) of selected neonicotinoids in the aquatic environment, using batch tests. Tests were carried out for acetamiprid individually and a mixture of five neonicotinoids (acetamiprid, clothianidin, imidacloprid, thiacloprid, and thiamethoxam), for three different aquifer materials and quartz sand. Based on the obtained values of the sorption parameters, the greatest sorption of neonicotinoids was observed on soil with the highest content of organic matter and clay minerals content, while no sorption of these pesticides was observed on quartz sand. In addition, it was noticed that individual neonicotinoids undergo sorption to a different degree — thiacloprid was the most sorbed (R-value in the range 3.13–26.03), while thiamethoxam was the least (R-value in the range 1.89–8.41).